The Biological Station - David Carlin (2018)
Research Background This research is located within the field of literary nonfiction practice, where personal essay intersects travel writing. Theorists of the personal essay, from Adorno to Shields, have argued that the genre can be a way of making accounts of the real that refuse to ignore the locations (embodied, institutional, cultural, and so on) from which the essayist speaks. How can the analytic and expressive techniques of the personal essay be considered alongside new materialist concepts such as atmospheric attunement (Stewart) as a way to respond to the experience of encounter with(in) a foreign place, and how might this suggest new directions for travel writing? Contribution The Biological Station takes an experience of travel-the residency of a white settler Australian at the Kilpisjarvi Biological Station in northern Finland-as material to generate an affective engagement with ideas of home, displacement and the possibilities of 'foreign' encounter, through novel use of the personal essay form. Ethnographic observation and thick description (Geertz) of the atmospheric (in all senses) conditions of the station and associated encounters are braided (Walker) with emergent childhood scenes of performance and sanctuary. Using Bachelard's The Poetics of Space as textual intermediary, the Station becomes a site of quiet wonder and connection. Significance This essay was simultaneously accepted for publication by two international (US-based) creative writing journals: Panorama: the Journal of Intelligent Travel and Hunger Mountain: The VCFA Journal for the Arts. Awarded Runner up in the international 2018 Hunger Mountain Creative Nonfiction Prize, it was subsequently published in that journal. Contest judge, noted US novelist Pam Houston, praised the essay for "its devotion to landscape and its willingness to gauge in the subtleties of human interaction, and the link between the two. It took me back to a beloved short story, "Aquifer," by Tim Winton."